Can't get the staff. (Economist, 1996)
Focuses on the shortage of manpower in different professions in Great Britain. Exaggeration of the number of vacancies as employment agencies are changing to a new computer system. Difficulty in finding experienced staff in the catering industry; Increase in demand for experiences computer programmers.